Changes to the genetic counseling workforce as a result of the COVID‐19 pandemic. Issue 5 (29th July 2021) - MacFarlane, Ian; Johnson, Amber; Zierhut, Heather
Abstract: The COVID‐19 pandemic has affected all aspects of our lives. The full impact of the pandemic is still unfolding and will take years to fully understand. This longitudinal study followed a sample of 189 genetic counselors from June to November of 2020, starting with an online retrospective baseline survey of pre‐COVID‐19 functioning and continuing with a monthly online survey (average retention = 89.2%) to assess changes in self‐reported stress, employment status, billing practices, self‐efficacy, and their use of telehealth. Participants were recruited from specific states representing geographic diversity with publicly available databases of contact information as well as social media. The sample was largely reflective of the professional demographics reported in the 2020 Professional Status Survey (PSS). Comparisons were made between the PSS, baseline assessment of pre‐COVID‐19 status, June, and November data. Genetic counselor workload did not significantly change in terms of hours worked from baseline to November, though patients served per week dropped initially before returning to pre‐COVID‐19 levels. Genetic counselors were increasingly working remotely and supervising students less frequently in November compared to pre‐COVID‐19 baseline. Approximately 50% of the sample were unable to bill for services throughout the study period, with billing practices not changing during this time. Approximately 40% experienced a negative employment change in June, which dropped to ~10% in November. Personal and family stress levels were elevated during the study period, while financial stress increased from baseline to June it returned to pre‐COVID‐19 levels by November. Self‐efficacy for common genetic counseling skills decreased from baseline to June but returned to baseline levels by November. The results suggest the workforce faced transitions but has rebounded in most areas studied. The pandemic highlighted pre‐existing billing issues, and the current billing structures were not able to shift in the face of practice transitions. The long‐term implications of the pandemic remain to be seen, but the results indicate returns toward baseline data in most areas with the exceptions of supervision, personal and family stress, and billing.